Effects of substance P on human cerebral microvascular endothelial cell line hCMEC/D3 are mediated exclusively through a truncated NK-1 receptor and depend on cell confluence. (October 2022) - Gao, Xin; Frakich, Nanci; Filippini, Perla; Edwards, Laura J.; Vinkemeier, Uwe; Gran, Bruno; Tanasescu, Radu; Bayraktutan, Ulvi; Colombo, Sergio; Constantinescu, Cris S.
Abstract: The neuropeptide substance P (SP) mediates pain transmission, immune modulation, vasodilation and neurogenic inflammation. Its role in the peripheral nervous system has been well characterised. However, its actions on the blood-brain barrier (BBB) are less clear and warrant further study. The aim of this study was to characterise the effect of SP on the brain microvascular endothelial cells using the immortalized human brain microvascular endothelial cell line hCMEC/D3. As part of our studies, we have evaluated changes in expression, at mRNA and protein levels, of genes involved in the function of the blood-brain barrier such as occludin, induced by exposure to SP. We show that the effect of SP is dependent on cell confluence status. Thus, at low confluence but not at full confluence, SP treatment reduced occludin expression. The expression of the SP receptor, neurokinin-1 receptor (NK-1R) (the truncated form of the receptor expressed exclusively in this cell line) was also modulated in a similar pattern. SP treatment stimulated extracellular signal-regulated kinase (Erk2) phosphorylation which was not associated to changes in Interleukin-6 (IL-6), Interleukin-8 (IL-8), or Intercellular Adhesion Molecule 1 (ICAM-1) protein expression. In addition, SP treatment effectively recovered nitric oxide production on cells exposed to tumour necrosis factor alpha (TNF-α). SP did not trigger intracellular calcium release in hCMEC/D3 cells. We conclude that hCMEC/D3 cells are partially responsive to SP, that the effects are mediated through the truncated form of the receptor and are dependent on the confluence status of these cells.